Distinct patterns of bank erosion in a navigable regulated river. Issue 2 (16th December 2019) - Duró, Gonzalo; Crosato, Alessandra; Kleinhans, Maarten G.; Winkels, Timotheus G.; Woolderink, Hessel A.G.; Uijttewaal, Wim S.J.
Abstract: Distinct bankline patterns appeared after the removal of protection works along a navigable reach of the Meuse River. A series of oblique embayments now dominate the riverine landscape after ten years of bank erosion, but their location and asymmetry cannot be explained yet. This work analyses and integrates field measurements of flow, ship waves, bank composition, bed topography and historical maps to explain the observed patterns along two reaches of the river. An extraordinary low‐water‐level event generated by a ship accident provided the unique opportunity to also analyse the subaqueous bank topography. The results indicate that the formation of oblique embayments arises from the combination of floodplain heterogeneity, structured by scroll‐bar deposits, and the regulation of water levels, resulting in ship‐wave attack at a narrow range of bank elevation for 70% of the time. Substrate erodibility acts on the effectiveness of trees to slow down local bank erosion rates, which is possibly enhanced by a positive feedback between woody roots and cohesive soil. The strong regulation of water levels and the waves generated by the intense ship traffic produce an increasingly long mildly‐sloping terrace at the bank toe and progressively dominate the bank erosion process. This study demonstrates the important role of floodplain and scroll bar formation in shaping later bank erosion, which has implications for predictive numerical models, restoration strategies, and understanding the role of vegetation in bank erosion processes. © 2019 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd Abstract : Banks with large embayments shape restored reaches of the Meuse River. A combination of floodplain heterogeneity and the regulation of water levels controlled their appearance, while ship waves formed a mildly sloping terrace. This demonstrates the important role of floodplain and scroll bar formation in shaping later bank erosion, having implications for predictive numerical models, understanding the role of vegetation in bank erosion processes, and planning restoration strategies.